2017
DOI: 10.1021/acs.molpharmaceut.6b00919
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Multivalency Enhances Affibody-Based HER3 Inhibition and Downregulation in Cancer Cells

Abstract: The receptor tyrosine kinase HER3 has emerged as a therapeutic target in ovarian, prostate, breast, lung, and other cancers due to its ability to potently activate the PI3K/Akt pathway, especially via dimerization with HER2, as well as for its role in mediating drug resistance. Enhanced efficacy of HER3-targeted therapeutics would therefore benefit a wide range of patients. This study evaluated the potential of multivalent presentation, through protein engineering, to enhance the effectiveness of HER3-targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
2
15
3
Order By: Relevance
“…This is particularly interesting, because our findings contradict data published by Schardt et al [27,28], who investigated the therapeutic efficacy of multivalent anti-HER3 affibody constructs using the HER3-binding variant Z 05413 . The authors hypothesized that dimerization would improve affinity through avidity and potentially increase the inhibition of HER3 phosphorylation, downstream signaling, and tumor progression and therefore improve the therapeutic efficacy [27,28]. Indeed, the authors demonstrated a significant reduction in tumor progression compared to controls for groups treated with bivalent affibody constructs but not with monovalent constructs [27].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…This is particularly interesting, because our findings contradict data published by Schardt et al [27,28], who investigated the therapeutic efficacy of multivalent anti-HER3 affibody constructs using the HER3-binding variant Z 05413 . The authors hypothesized that dimerization would improve affinity through avidity and potentially increase the inhibition of HER3 phosphorylation, downstream signaling, and tumor progression and therefore improve the therapeutic efficacy [27,28]. Indeed, the authors demonstrated a significant reduction in tumor progression compared to controls for groups treated with bivalent affibody constructs but not with monovalent constructs [27].…”
Section: Discussioncontrasting
confidence: 74%
“…While several HER3-targeting therapeutic agents are currently under preclinical and clinical development, no HER3-specific drugs or treatments have yet been approved [12]. Efforts by our group and others have demonstrated in preclinical models that anti-HER3 affibody molecules could be an alternative for HER3-targeted therapy [21,27,28]. For example, the affibody construct TAM-HER3 (an ABD flanked by two HER3-binding affibody molecules) delayed the growth of HER3 expressing tumors in a mouse model with equal potency as the HER3-targeting antibody MM-121 [21], indicating the main mode of action is based on receptor blocking and is not Fc-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their small size, affibody can be synthesized or recombinantly expressed. Since the first construct HER2-targeting affibody molecule Z HER2:342 was produced and confirmed to bind to HER2-positive cancer cell lines [24], several similar affibody molecules targeting EGFR [23,24], HER3 [27,28], IGF-1R [42], HIV-1-gp120 [43] and HPV16E7 [30,31] have been reported and also applied to image several tumour-associated molecular targets, such as HER2 [25,44], EGFR [45,46], HER3 [47]. The first clinical imaging study on patients with breast cancer was conducted using HER2-specific affibody, which Mice bearing C666-1tumor grafts were intravenously injected with 100 nmol/kg Z142X, Z142, or an equal amount of control agents or the same volume of PBS every two days for 15 times via tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 400 published studies show that affibody molecules have been selected for targeting more than 40 different proteins and served as affinity moieties in a variety of applications [22]. The affibody-targeted proteins include epidermal growth factor receptor (EGFR) [23,24], human epidermal growth factor receptor 2 (HER2) [25,26], human epidermal growth factor receptor 3 (HER3) [27,28], vascular endothelial growth factor (VEGF) [29], and human papillomavirus type 16 E7 (HPV16E7) [30,31]. In particularly, affibody molecules attached with a cytotoxin appear to be a straightforward and efficient way to direct the action of the toxin to desired cell targets [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that multivalent constructs could provide increased therapeutic potential compared to monomeric analogues. Indeed, in vitro the bi- and trivalent HER3-specific affibody molecules were significantly more efficient in blocking phosphorylation of HER3 and inhibiting cellular activity and proliferation compared to the monovalent control [ 20 , 26 ]. We demonstrated that a bivalent construct based on an anti-HER3 affibody molecule fused with ABD, 3A3, also efficiently inhibited growth of HER3-expressing cells in vitro, had prolonged in vivo half-life, delayed growth of HER3-expressing BxPC-3 xenografts in mice, and was equipotent to seribantumab (MM-121) [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%